Effect of unconventional feeds on production cost, growth performance and expression of quantitative genes in growing pigs - U. G. Sorhue; I. O. Israel; A. M. Moemeka; I. S. Omeje; I. Udeh; C. V. Idama; F. Awolowo (Journal of the Indonesian Tropical Animal Agriculture, 2022)
This study examined the effects of unconventional feed on performance characteristics and candi-date gene expression in growing pigs of 3-5months of age. A Total of forty-five (45) growing pigs were randomly allotted into five treatments consisting of whole maize (T1), brewer’s dried grain (T2), cassava peel meal (T3), plantain peel meal (T4), and corn husk meal (T5), at 35% inclusion rate. Per-formance data were collected for 12weeks, while duodenum and liver samples were collected after the experiment for gene expression analysis. Data were analyzed in a completely randomized design. Diets significantly (p< 0.05) affected growth performance with treatment 2 recording the highest average daily weight gain of 0.21±0.02 whilecorn husk meal (T5)had the least 0.11±0.01. Feed efficiency was highest for whole maize (T1) and brewer’s dried grain (T2) (0.10±0.02) and lowest for t5 (0.07±0.17). Cost-benefit analysis were significantly different (p<0.05) with t4 recording the highest gross margin. Insulin-like growth factor1 and leptin gene were differentially expressed in tissues, while no significant differences (p>0.05) existed for growth hormone gene and ryanodine receptor1 gene. The results showed commendable gross margin, however, cognizance should be taken in the quantity of brewer’s dried grain fed to pigs since it increased the expression of ryanodine receptor 1 gene that leads to por-cine malignant hypertermia and pale soft exudates pork.